Lower Cretaceous provenance in the northern Austral basin of Patagonia from sedimentary petrography - Barberon, Vanesa (2015)
The northern Austral basin from Patagonia is characterized by an Early Cretaceous (Barremian–Albian) coarse-grained regressive sequence. These littoral to continental deposits conform a 150 km long basin cropping out along the Southern Patagonian Andes between 47 and 48°S. The basin fill consist of basal deltaic sandstones with interbedded shales and limestones from the Río Belgrano Formation, topped by up to 350 m of fluvial conglomerates and reworked tuffs of the Río Tarde and Kachaike formations. This continental depocenter represent a major geodynamic and paleoenviromental change from the underling marine Río Mayer Formation. In this study we analyze the tectonic setting and provenance during deposition of the coarse-grained sequence using sedimentary petrography of 37 thin sections in four stratigraphic profiles covering the northern basin. Our dataset indicates mainly a recycled orogenic sandstones provenance, in agreement with potential surrounding basement sources.